O eu e o outro nas memórias dos becos : a alteridade na resistência poética de Cora Coralina - (:unkn) unknown (Universidade Estadual de Goiás, 2022)
This paper seeks to analyze the representations of the other that are pointed out in Poemas dos becos de Goiás e estórias mais, as a representation of life and resistance in the voice of the Goiás poet and storyteller, Ana Lins dos Guimarães Peixoto Bretas, baptized by herself as Cora Coralina, who in the saying of the poet ―I didn't want to be confused with the abundance of names Anas, Aninhas and Anocas‖ originating from her name. The investigation seeks interconnections in the writing of a poet who breaks the barriers of her time and prejudice in a reality experienced in alleys delimited by classes, having as a cradle a sexist, racist and excluding society, bringing the view of the alley from a fragmentary perspective of anonymous individuals and showing their afflictions, pains and difficulties. In this way, several characters are researched, such as: the prostitute, the washerwomen, the alleys and the woodworking boys, icons of the Cidade de Goiás, Goiás, Brazil, who are people whom the poet remembers. In this context, from theoretical discussions, the nature of this research is qualitative descriptive in relation to the object of study: the alley, with surveys of elements of social structure, memory and time. And, still, in an analytical and comparative method, as there is a relationship between the lyrical subject, at a time, and the memory of many characters articulated in a fictional space, lived and remembered by Cora Coralina. A path of bibliographic nature is sought, with several theorists being named some authors who make this approach possible: Bosi (1994), Kossoy (1999) Assmann (2011) and Candau (2019) among others who examine the place of the other and end up highlighting in culture and society such realities lived along the human trajectory.
The me and another one into memories of alleys : the alterity in Cora Coralina's poetry resistance
Keywords: Cora Coralina; Poesia; Beco; Memória; Resistência; Poetry; Alley; Memory; Resistance; LETRAS::LITERATURA BRASILEIRA